Efeito do probiótico Saccharomyces boulardii em gerbils (Meriones unguiculatus) experimentalmente infectados com Giardia lamblia - Mayana Rodrigues dos Santos Ribeiro (2015)
Giardia lamblia is a protozoan that causes giardiasis, one of the most common causes of diarrhea in humans. Many of the adverse effects are given to the conventional treatment, which results in significant disruption thereof. This study evaluated the action of probiotic Saccharomyces boulardii in the parasite load of gerbils experimentally infected with G. lamblia. 28 gerbils (Meriones unguiculatus), male, 4 to 6 weeks were divided into 4 groups: Control (CT); Infected (INT); S. boulardii (SB); Infected treated with S. boulardii (ISB). The SB and ISB groups received, by gavage, 1x109/0.1 CFU/0,1 mL de S. boulardii suspension in PBS, 1 once/day for 15 days. After this period, the INT and ISB groups were challenged by gavage with 1 x 10 6 trophozoites / ml of BHRA-93 strain of G. lamblia. Until the 23rd day of the experiment the ISB and SB animals continued to receive the probiotic, whereupon all were euthanized. The proximal small intestine was collected, fixed and processed for staining with Hematoxylin & Eosin (HE), Periodic Acid-Schiff (PAS) and immunohistochemistry. The height and width of the villi, the crypt depth, the area of mucus and trophozoites area were calculated using the ImageJ software. Results were expressed as mean ± standard deviation, using the normality test Shapiro-Wilk, analysis of variance and Tukey test for comparison between groups. The statistical package GraphPad Software 6.0 was used. Significant reduction in worm burden was observed in the group ISB 2.2 x 105 ± 1.8 x 105 INT group compared to 8.16 x 105 ± 4.2 x 105 trophozoites / ml (p <0.01). The trophozoites immunoblotted area was also lower in the ISB group 1.48 ± 3.29 x 103 μm² in relation to the INT group 4.96 ± 6.78 x 103 μm² (p <0.05). The animals treated only with probiotics (SB group) had significantly higher villus height that the animals in the other groups; No differences were found with regard to width of villi and crypts high. Regard to mucus production area of groups SB and ISB was higher compared to the CT and INT groups (p <0.01). INT group had fewer goblet cells compared to other groups (p<0.01). The CT group presented a smaller number of intraepithelial lymphocytes compared to the INT and ISB groups p <0, 01. It was also observed greater intraepithelial lymphocytes number on the ISB group compared to the INT group (p <0.01). Our results showed a protective effect of S. boulardii in giardiasis prompting new studies to understand the mechanisms involved in this protection.